Wideband Acoustic Immittance in Cochlear Implant Recipients: Reflectance and Stapedial Reflexes. Issue 4 (July 2020) - Scheperle, Rachel A.; Hajicek, Joshua J.
Abstract : Objectives: to characterize differences in wideband power reflectance for ears with and without cochlear implants (CIs), to describe electrically evoked stapedial reflex (eSR)-induced changes in reflectance, and to evaluate the benefit of a broadband probe for reflex threshold determination for CI recipients. It was hypothesized that reflectance patterns in ears with CIs would be consistent with increased middle ear stiffness and that reflex thresholds measured with a broadband probe would be lower compared with thresholds obtained with a single-frequency probe. Design: Eleven CI recipients participated in both wideband reflectance and eSR testing. Ipsilateral reflexes were measured with three probes: a broadband chirp (swept from 200 to 8000 Hz), a 226 Hz tone, and a 678 Hz tone. Wideband reflectance measures acquired from 28 adults without CIs and with normal middle ear function served as a normative data set for comparison. Results: Considering the group data, average reflectance was significantly greater for ears with CIs across 250 to 891 Hz and 4238 to 4490 Hz compared with the normative data set, although individual reflectance curves were variable. Some CI recipients also had low 226 Hz admittance, which contributed to the group finding, considering the control group had clinically normal 226 Hz admittance by design. Electrically evoked stapedial reflexes were measurable in nine of 14 ears (64.3%) and in 24 of 46 electrodes (52.5%) tested. Reflex-induced changes in reflectance patterns were unique to the participant/ear, but similar across activators (electrodes) within a given ear. In addition, reflectance values at or above 1000 Hz were affected most by activating the stapedial reflex, even in ears with clinically normal 226 Hz admittance. This is a higher-frequency range than has been reported for acoustically evoked reflex-induced reflectance changes and is consistent with increased middle ear stiffness at rest. Electrically evoked reflexes could be measured more often with the 678 Hz or the broadband probe compared with the 226 Hz probe tone. Although reflex thresholds were lower with the broadband probe compared with the 678 Hz probe in 16 of 24 conditions, this was not a statistically significant finding (Wilcoxon signed-rank test; p = 0.072). Conclusions: The applications of wideband acoustic immittance measurements (reflectance and reflexes) should also be considered for ears with CIs. Further work is needed to describe changes across time in ears with CIs to more fully understand the reflectance pattern indicating increased middle ear stiffness and to optimize measuring eSRs with a broadband probe. Abstract : Supplemental Digital Content is available in the text.